Association of gestational diabetes mellitus diagnosed at different time points in oral glucose tolerance test with adverse pregnancy outcomes: a retrospective cohort study - Lin, Ruipeng; Zhang, Yulong; Lin, Yuxin; Yang, Lili; Chen, Jiayi; Li, Qingxiu; Li, Haibo; Zhang, Qian (Frontiers in Endocrinology, 2025)
BackgroundThis study aims to explore the association between gestational diabetes mellitus (GDM) diagnosed at different time points in the oral glucose tolerance test (OGTT) and adverse pregnancy outcomes (APO).MethodsA retrospective cohort study based on the 75g OGTT conducted in Fujian Maternity and Child Health Hospital. GDM was diagnosed if plasma glucose levels exceeded the threshold at any time point (5.1 mmol/L at 0h, 10.0 mmol/L at 1h, and 8.5 mmol/L at 2h). Binary logistic regression and subgroup analysis were used to analyze the association between abnormal plasma glucose in OGTT and APO.ResultsThe study included 37,598 normal pregnancies and 11,302 APO. Compared to the normal group, pregnant women with GDM and abnormal plasma glucose at different time points had an increased risk of APO. Group 2 (abnormal at 0h, but normal at 1h and 2h), Group 3 (normal at 0h, but abnormal at 1h or 2h), and Group 4 (abnormal at 0h, 1h or 2h) showed an increasing trend in APO risk compared to Group 1 (normal at three time points), with adjusted OR of 1.14, 1.18, and 1.42, respectively (P<0.001). The subgroup analysis showed no statistically interaction, and the sensitivity analysis results were stable.ConclusionAbnormal plasma glucose at different time points is associated with the risk of APO, with the highest risk observed in those with abnormalities at all time points. Future health management for high-risk pregnant women should be strengthened by considering abnormal plasma glucose at different time points.